2021
DOI: 10.1039/d1cc05609c
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed allylative dearomatisation using Grignard reagents

Abstract: Dearomatisation of benzylic halides have been achieved using Grignard reagents resulting in good isolated yields in short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The only reported non-radical reaction is a sigmatropic rearrangement of propargyl substituted semibenzene to allenyl benzenes . Alternatively, it has also been shown that non-fully substituted semibenzenes quickly react in the presence of acids to yield the rearomatized compounds (by elimination of H + from the sp 3 carbon). ,, In the 1980s, an analogous rearomatization was reported by the group of Reutov (Scheme b), who found that semibenzenes would form the corresponding benzylic organometallic reagent upon reaction with transition-metal salts (mainly Hg, but also Sn, Ge, and Au), in a so-called aromative metalation. , …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The only reported non-radical reaction is a sigmatropic rearrangement of propargyl substituted semibenzene to allenyl benzenes . Alternatively, it has also been shown that non-fully substituted semibenzenes quickly react in the presence of acids to yield the rearomatized compounds (by elimination of H + from the sp 3 carbon). ,, In the 1980s, an analogous rearomatization was reported by the group of Reutov (Scheme b), who found that semibenzenes would form the corresponding benzylic organometallic reagent upon reaction with transition-metal salts (mainly Hg, but also Sn, Ge, and Au), in a so-called aromative metalation. , …”
Section: Introductionmentioning
confidence: 78%
“…Semibenzenes (3-methylenecyclohexa-1,4-dienes) are a class of unstable compounds often overlooked by chemists since they are challenging to synthesize and work with. However, in 2001, seminal work by Yamamoto et al provided a remarkable turnaround in this regard, showing that the synthesis of mono- and di-substituted allylated semibenzenes is rather straightforward via Pd-catalyzed dearomative allylation of benzylic halides . Various modified and improved procedures have been reported since, but synthetic applications of semibenzenes remain scarce to this day. The only examples were reported by the group of Yamaguchi (Scheme a), namely, a cyclopropanation and an oxidation of the external double bond of semibenzenes, leading to the corresponding alcohols or α,β-unsaturated carbonyls. , …”
Section: Introductionmentioning
confidence: 99%
“…2 This method complements traditional functionalization of aromatic rings, providing convenient access to complex cyclic nonaromatic and aromatic systems. In addition to benzyl chlorides, 1,3 benzyl phosphates, 4 benzyl carbonates, 5 benzylammonium salts, 6 and N -benzylsulfonimides 7 have later proved to serve as alternative benzyl electrophiles (Scheme 1). On the other hand, the dearomative allylation or the aromatic C–H allylation of benzyl electrophiles was successfully extended to allylsilanes, 3 c allylboronates, 3 d ,4 and allyl Grignard reagents.…”
mentioning
confidence: 99%
“…Meanwhile, the dearomative allylation of aromatic C–H bonds for benzyl electrophiles is well-studied . Benzyl halides, benzyl phosphates, , and benzyl ammonium analogs , undergo the dearomative para -allylation (Figure B). However, with the exception of one intramolecular iridium-catalyzed transformation (Figure C), these reactions require unsubstituted organometallic allyl nucleophiles and a leaving group at the benzylic position, thus featuring a limited scope and low atom economy.…”
mentioning
confidence: 99%